Epidemiology of virus-induced asthma exacerbations: with special reference to the role of human rhinovirus - Saraya, Takeshi; Kurai, Daisuke; Ishii, Haruyuki; Ito, Anri; Sasaki, Yoshiko; Niwa, Shoichi; Kiyota, Naoko; Tsukagoshi, Hiroyuki; Kozawa, Kunihisa; Goto, Hajime; Takizawa, Hajime (Frontiers in Microbiology, 2014)
Viral respiratory infections may be associated with the virus-induced asthma in adults as well as children. Particularly, human rhinovirus is strongly suggested a major candidate for the associations of the virus-induced asthma. Thus, in this review, we reviewed and focused on the epidemiology, pathophysiology, and treatment of virus-induced asthma with special reference on human rhinovirus. Furthermore, we added our preliminary data regarding the clinical and virological findings in the present review.